2020
DOI: 10.17977/um048v26i2p66-72
|View full text |Cite
|
Sign up to set email alerts
|

Talking Stick Learning Model, How Significant Has the Impact on the PGSD Students’ Speaking Skills?

Abstract: This is an open access article under the CC-BY license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…The researchers found that the talking stick technique was beneficial in teaching speaking and can improve learners' speaking performances (Al-Qarawi, 2018;Suseno et al, 2020). Using a talking stick encourages learners to voice their thoughts and opinions (Sartipa, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers found that the talking stick technique was beneficial in teaching speaking and can improve learners' speaking performances (Al-Qarawi, 2018;Suseno et al, 2020). Using a talking stick encourages learners to voice their thoughts and opinions (Sartipa, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Putu Utari juga memaparkan bahwa model talking stick dapat melatih kemampuan kognitif siswa untuk menyusun bahasa yang dapat diutarakan mewakili pikiran mereka dan lebih meningkatkan kreativitas siswa dalam mengungkapkan gagasan yang mereka miliki (Sukmadewi & Ganing, 2020). Loviniantika juga menemukan hasil penelitiannya yang menyatakan bahwa penerapan model talking stick ini dapat meningkatkan keterampilan siswa dalam berbicara sehingga ilmu yang telah mereka pahami dapat juga mereka sampaikan kepada teman-temannya (Suseno et al, 2020).…”
Section: Pembahasanunclassified